Malariometric Survey Among Elementary School Children Aged 6-9 Years in Sangihe Besar - Laurentz R.; Paul S. Manoempil (Paediatrica Indonesiana, 1996)
One of the most common classification of malaria transmission in particular area is based on the levels of endemicity. It could be quantified by determination of chilÂdren with enlarged spleens and parasitemia. A "Cross sectional study" was carried out with the purpose of finding out the proportion of elementary school children aged 6-9 years with enlarged spleen and parasitemia and the influence of frequency of illnesses related to malaria. The samples were selected by basing on "standard cluster sampling technique". Out of 500 elementary school children, the spleen rate, parasite rate and avÂerage of enlarged spleens (AES) were 12.2 %, 8.6 % and 1.49, respectively. The highest spleen rate and parasite rate were found in Manalu subdistrict. There were significantly correlation between enlarged spleens and parasitemia (p < 0.05); parasitaemia and freÂquency of illnesses (p < 0.05); frequency of illnesses and enlarged spleens (p < 0.005).